Design and implementation of a controlled low-cost ventilator for emergency use on ICU patients - Ruiz-Barquero , Anibal (2024)
The worldwide outbreak of the SARS-CoV-2 virus led to a shortage of hospital ventilators worldwide. During recovery, these devices were crucial for patients in Intensive Care Units (ICUs). However, countries like Costa Rica faced difficulties acquiring these devices due to high demand in the world. To address this issue, professionals and students from the Costa Rica Institute of Technology have developed a prototype of a mechanical ventilator. This ventilator incorporates PIDs and Fuzzy Logic algorithms and features a user-friendly graphic interface based on PyQt5/GraphicsView, designed with input from medical experts. The ventilator is easy to assemble and highly portable. Initially, the ventilator successfully underwent testing using advanced patient simulators, namely Gaumard HAL S3201 and Gaumard NOELLE S574.100. Subsequently, it underwent a successful real-world test using animals. The tests involved varying the breathing rate from 10 to 30 breaths per minute, adjusting the tidal volume from 250 to 800 mL with automatic control of a 50 mL increase, and manipulating the I: E ratio from 1:1 to 1:5.